Designing for Continued Use of Digital Interfaces - Guidelines for Designing a Selection Mechanism Used in a Multi-Layered Interface to Aid Continued Use of Digital Interfaces Targeting Digital Seniors - Finne, Rebecca; Larsson, Lisa (My University, 2020)
Technology is more and more becoming part of today’s society and having a digital device and access to the internet is today a requirement to not be excluded from society. However, using a digital product is not as easy when growing older since physical and cognitive skills are decreasing with age. To help older adults continue using their social media a research group has started a project where they are exploring the possibility of using a technique called multi-layered design. This technique divides the functionality of an interface into different layers making it possible to remove unnecessary features for certain users and by that make an interface easier to use. As a part of this project, we have researched how to best implement a selection mechanism that decides which layer in the multi-layered design is best suited for each user. The final result has been found by conducting interviews, researching literature, and creating a questionnaire. A final prototype with seven functionality groups containing layers was created and tested. The prototype is a wizard where the user answers questions and depending on their answers they get a customized Facebook interface. The user tests showed that the participants liked the concept and they said that they were likely to use something similar if it were to be implemented by Facebook. Based on the findings from the user tests, eight guidelines were created. These can be seen as guidance when designing a selection mechanism for multi-layered interfaces to help digital seniors to continue to use a computer program. However, further testing by a long-term study is needed to see how the seniors would interact with the prototype in the wild and how their reactions to the layers are when having a chance to use Facebook as they usually do.
Keywords: multi-layered interface; digital seniors; adaptable interface; selection mechanism; Facebook